E-Groceries Market in Indonesia: Opportunities and Challenges - Myrza Febi; Leonnard Ong (Journal of Sustainable Community Development (JSCD), 2025)
The rapid expansion of Indonesia’s digital economy is reshaping grocery shopping, with egroceries emerging as a high-growth channel. Rising internet access, smartphone use, and busier urban lifestyles are shifting demand online for convenience, competitive prices, and broader assortments. Marketplaces and dedicated e-grocery operators now compete on speed and reliability, enabled by advances in logistics, inventory visibility, and payments. E-service quality is the key differentiator: intuitive interfaces, secure checkouts, responsive support, accurate fulfilment, and dependable delivery build trust and repeat purchase—especially for perishables. Expectations are moving beyond fast to transparent order tracking, personalized offers, and flexible payment and delivery options. COVID-19 accelerated adoption by firsttime users, yet structural challenges remain uneven infrastructure outside major cities, costly last-mile operations, and intense price competition that compresses margins. Maintaining onshelf availability and consistent quality control is critical to satisfaction and loyalty. Future growth will be shaped by tighter collaboration among retailers, technology providers, and logistics partners. Players that pair superior e-service standards with disciplined supply-chain execution can convert trial into habit, deepen brand loyalty, and sustain profitable scale. As urbanization continues and digital literacy rises, e-groceries are positioned to become a mainstream pillar of Indonesia’s retail landscape.